The Effect of Channel Estimation Error on the Performance of Spatial Media-Based Modulation Systems - Kabaci, Akif; Basaran, Mehmet; Çirpan, Hakan Ali (IEEE, 2021)
This paper investigates the performance of channel estimation models with an assumed fixed error with respect to the reference signal-aided channel estimation in the matter of spatial media-based modulation (SMBM) systems. For both cases, SMBM system performance is presented by average bit error rate simulations and the closed-form expressions of error upper bounds in Reyleigh fading channels. It has been observed that the error upper bounds obtained with the simulation results are quite compatible with analytical results for both cases. This study is important in terms of observing the system performance between reference signal-aided channel estimation and fixed error channel estimation models in SMBM systems for the first time.